An epidemiological investigation of Campylobacter in pig and poultry farms in the Mekong delta of Vietnam. - Carrique-Mas, J; Bryant, J; Cuong, N; Hoang, N; Campbell, J; Hoang, N; Dung, T; Duy, D; Hoa, N; Thompson, C; Hien, V; Phat, V; et al. (Cambridge University Press, 2014)
Campylobacter are zoonotic pathogens commonly associated with gastroenteritis. To assess the relevance of Campylobacter in Vietnam, an economically transitioning country in SE Asia, we conducted a survey of 343 pig and poultry farms in the Mekong delta, a region characterized by mixed species farming with limited biosecurity. The animal-level prevalence of Campylobacter was 31·9%, 23·9% and 53·7% for chickens, ducks and pigs, respectively. C. jejuni was predominant in all three host species, with the highest prevalence in pigs in high-density production areas. Campylobacter isolates demonstrated high levels of antimicrobial resistance (21% and 100% resistance against ciprofloxacin and erythromycin, respectively). Multilocus sequence type genotyping showed a high level of genetic diversity within C. jejuni, and predicted C. coli inter-species transmission. We suggest that on-going intensification of animal production systems, limited biosecurity, and increased urbanization in Vietnam is likely to result in Campylobacter becoming an increasingly significant cause of human diarrhoeal infections in coming years.